The post-war style of citizens of the Polish Republic and the GDR - Zawadzka, Justyna (Free your mind: Reflections on language, literature and culture, 2022)
Text “The post-war style of citizens of Polish Republic and GDR” by Justyna Zawadzka is a comparative analysis of fashion and culture development after World War II in the Polish Republic and German Democratic Republic. The analysis was based on Anna Pelka’s 2013 publication “Z politycznym fasonem”. The text is divided into decades, in which the style of citizens of both countries was created and changed, until the end of the 1980s. An analysis of both men’s, women’s and youth styles was undertaken.